Mladinska dela Aksinje Kermauner - Haramija, Dragica (Jezik in slovstvo, 2008)
To date, Aksinja Kermauner has published ten literary works in book form dedicated to children and young adults. Her works are classified in the following literary genres: most of her texts fall into the category of prose, namely realistic short stori es, imaginary stori es, social-psychological young-adult novel, classic fairy tale and realistic narrative; the author has also published the text for a play (a puppet show) and an informative picture book on blindness and impaired vision. The theme she is primarily concerned with is the relationships between people with unimpaired senses and those with special needs. The author introduces elements of humour into her work, and especially optimism, which in contemporary society seems to be somewhat anachronistic. The same is true of the continuous recalling of the importance of friendship, understanding among people (particularly overcoming generational conflicts), and environmental care.
Keywords: bibliografije; children's literature; Kermauner; Kermauner, Aksinja; mladinska književnost; otroška književnost; slikanice; Slovene literature; slovenska književnost; slovenske pisateljice; Taras Kermauner; young adult literature